2021
DOI: 10.3390/ani11051379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cryptorchidism on the Histomorphometry, Proliferation, Apoptosis, and Autophagy in Boar Testes

Abstract: Spontaneous unilateral cryptorchid boars have one testis in the abdomen or inguinal canal, causing its temperature to be at or near the body temperature, which impairs spermatogenesis, although the histomorphometry and molecular mechanisms underlying this process remain unclear. The aim of the present study was to determine the histomorphometry, proliferation, apoptosis, and autophagy alterations in spermatogonia and Sertoli cells in unilateral cryptorchid, scrotal (contrascrotal), and preweaning piglet (prewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In the cryptorchid male gonad, the localization of OXB and OX2R is restricted to Leydig and Sertoli cells. That might be attributed to detrimental effects on spermatogenesis, due to the undescending testis which ultimately leads to infertility as already reported (21,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In the cryptorchid male gonad, the localization of OXB and OX2R is restricted to Leydig and Sertoli cells. That might be attributed to detrimental effects on spermatogenesis, due to the undescending testis which ultimately leads to infertility as already reported (21,(35)(36)(37).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, OXB was demonstrated to not affect steroidogenesis (15,16), thus its role remains unclear. The regulation of male fertility and differentiation depends on the testicular descent from the abdomen to the scrotum (21). In this regard, cryptorchidism is a testicular dysgenesis has been described as the failure of one (unilateral) or both (bilateral) testes and the relative spermatic ducts to migrate into the scrotum (22)(23)(24), that is found particularly in dogs (involving, to a greater extent, the right gonad) (25)(26)(27), stallions (21,23,28), and humans (29).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis, the programmed cell death, takes place during normal spermatogenesis. However, physical testicular injuries could elevate germ cell apoptosis and reduce seminiferous tubule diameter and sperm count ( 60 , 68 , 107 , 108 ). We observed that melatonin decreases apoptotic germ cells and ameliorates the detrimental impact of physical injuries on the testes.…”
Section: Discussionmentioning
confidence: 99%